Analyzing Critical Thinking Skills of Grade VIII Students in Human Respiratory System Topics in Junior High School - Yosefina Ngongo; Geterudis Kerans; Yulita Adelfin Lede (CV. Dharma Samakta Edukhatulistiwa, 2026)
Critical thinking skills are essential 21st-century competencies that need to be developed in science education. This study aims to analyze the critical thinking skills of grade VIII students in a junior high school on human respiratory system topics. This research employed a qualitative descriptive method involving 27 students. The research instruments consisted of an essay test developed based on Ennis's critical thinking indicators (basic clarification, bases for a decision, inference, advanced clarification, and strategies and tactics) as well as semi-structured interviews with six students selected through purposive sampling. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and drawing conclusions. The results showed that the majority of students possessed critical thinking skills in the low category: 22 students (81.48%) were in the low category, 3 students (11.11%) in the moderate category, and 2 students (7.41%) in the high category. These findings emphasize the need for implementing innovative learning strategies to enhance students' critical thinking skills in science learning.